A review: personal identification based on palm vein infrared pattern - Soh, Shi Chuan; M. Z., Ibrahim; Marlina, Yakno (UTeM, 2018)
Palm vein recognition is the latest biometrics technique used and researches currently. This method achieved high performance in identification due to the complexity of vein pattern on the palm. This studies proposed a review of overall process of vein recognition and vein recognition techniques. In particular, this studies is systematically described in three parts which is vein image acquisition and preprocessing, feature extraction and decision matching. According to the available work, various approaches for different kind of features extractions, palm vein segmentation and overall process will be discussed in this paper.